Standardized Uptake Value Using Thyroid Quantitative SPECT/CT for the Diagnosis and Evaluation of Graves' Disease: A Prospective Multicenter Study. (30th January 2019) - Dong, Feng; Li, Lin; Bian, Yanzhu; Li, Guoquan; Han, Xingmin; Li, Mei; Liu, Juzhen; Xue, Yong; Li, Yuhao; Hu, Yujing; Tan, Jian
Abstract : The clinical applications of the quantitative single photon emission computed tomography (SPECT)/computed tomography (CT) are being expanded to a variety of fields of nuclear medicine. However, clinical application of quantitative SPECT/CT for the evaluation of Graves' disease (GD) still needs further investigation. Our aim was to investigate the feasibility of standard uptake value (SUV) of the thyroid for the clinical diagnosis and evaluation of GD. In this prospective multicenter study, 116 patients diagnosed with GD (Graves group) and 74 healthy volunteers (control group) were enrolled from 8 different hospitals. All patients underwent technetium pertechnetate (T c O 99 m 4 - ) SPECT/CT imaging with Q.Metrix quantitative software and 24-hour thyroid radioactive iodine uptake (24h-RAIU) test. The SUVmax and SUVmean in Graves group were significantly higher than those of control group ( P <0.01). Cut-off values of SUVmax and SUVmean to predict GD were 231.425 and 116.66 by ROC curves, respectively. The SUVmax and SUVmean in Graves patients were significantly related to serum thyroxine level with correlation coefficient of 0.493 and 0.512 for FT3 and 0.449 and 0.464 for FT4, respectively (all P <0.01). Additionally, the SUVmax and SUVmean in GD positively correlated with 24h-RAIU with a coefficient of 0.832 and 0.830, respectively ( P <0.01). The volumes determined by Q.Metrix (35.65 ± 20.56ml) of 72 subjects also positively correlated with that from ultrasound (36.67 ± 21.00ml) with a coefficient of 0.927 ( P <0.01). SUV measurements derived from thyroid SPECT/CT may be useful for the clinical diagnosis and evaluation of GD.